The effectiveness of a training program to improve participation and empathy skills among the hearing impaired: A field study at the level of the fourth and fifth grades of primary school at the School for Young Deaf People, Tiaret Province: Sougueur Dist - abid, soumia; mahi, ibrahim (Journal of Social Sciences and Humanities, 2021)
The study aimed to detect the impact of the training program based on a set of active learning strategies to improve the level of participation and empathy skills in a sample of the experimental group of deep hearing impairment (deafness), and the sample of the experimental group consisted of 12 cases spread over two levels. For the purpose of collecting data, the researcher used a special measure of participation and empathy skill suppalling prepared by the researcher and a training program based on a set of active learning strategies for the purpose of improving the level of skill of participation and empathy in the sample The experimental method was adopted in one direction and for the analysis of the data was used the statistical package program (spss) and the results of the current study found that there are statistically significant differences for the two groups in favor of the dimensional application.